Development of the Duquesne University School of Nursing Sexual Assault Nurse Examiner Training Model. Issue 1 (17th January 2022) - Sekula, L. Kathleen; Colbert, Alison M.; Currie, Meghan
ABSTRACT: Introduction: Lack of preceptors and hands-on training opportunities has long been an impediment to nurses pursuing sexual assault nurse examiner (SANE) practice and certification after completing a SANE didactic course. In addition, nurses in rural and underserved areas often lack the professional support and mentoring needed. To address this gap and increase the number of certified practicing SANEs, the Duquesne University School of Nursing (DUSON) received funding from the Department of Health Resources and Services Administration for a program designed to provide advanced nursing education to increase the number of nurses who are trained and certified as nurse examiners. Approach: The DUSON developed a hands-on clinical preceptor course and other support programming to supplement the existing SANE didactic course training. The goal was to create a comprehensive model that took students from initial SANE training through to certification. Lessons Learned: In the first two- and three-quarter years of the program, 36 nurses achieved certification, and another 116 completed a didactic course and initial hands-on skills training and are preparing for certification. Approximately 41.5% of participants are from rural and/or underserved areas. Challenges included the adaptations required by the COVID-19 pandemic and engagement of nurses once they returned to their home institution to complete additional hours. Conclusions: The DUSON comprehensive model provides a solid pathway for nurses who want to become SANEs, and the structure of the program seems especially conducive for training nurses in rural and underserved areas.